Timing of surgery following neoadjuvant chemoradiotherapy in locally advanced rectal cancer – A comparison of magnetic resonance imaging at two time points and histopathological responses. Issue 9 (September 2016) - West, M.A.; Dimitrov, B.D.; Moyses, H.E.; Kemp, G.J.; Loughney, L.; White, D.; Grocott, M.P.W.; Jack, S.; Brown, G.
Abstract: Purpose: There is wide inter-institutional variation in the interval between neoadjuvant chemoradiotherapy (NACRT) and surgery for locally advanced rectal cancer. We aimed to assess the association of magnetic resonance imaging (MRI) at 9 and 14 weeks post-NACRT; T-staging (ymrT) and post-NACRT tumour regression grading (ymrTRG) with histopathological outcomes; histopathological T-stage (ypT) and histopathological tumour regression grading (ypTRG) in order to inform decision-making about timing of surgery. Patients and methods: We prospectively studied 35 consecutive patients (26 males) with MRI-defined resection margin threatened rectal cancer who had completed standardized NACRT. Patients underwent a MRI at Weeks 9 and 14 post-NACRT, and surgery at Week 15. Two readers independently assessed MRIs for ymrT, ymrTRG and volume change. ymrT and ymrTRG were analysed against histopathological ypT and ypTRG as predictors by logistic regression modelling and receiver operating characteristic (ROC) curve analyses. Results: Thirty-five patients were recruited. Inter-observer agreement was good for all MR variables (Kappa > 0.61). Considering ypT as an outcome variable, a stronger association of favourable ymrTRG and volume change at Week 14 compared to Week 9 was found (ymrTRG – p = 0.064 vs. p = 0.010; Volume change – p = 0.062 vs. p = 0.007). Similarly, considering ypTRG as an outcome variable, a greater association of favourable ymrTRG and volume change at Week 14 compared to Week 9 was found (ymrTRG – p = 0.005 vs. p = 0.042; Volume change – p = 0.004 vs. 0.055). Conclusion: Following NACRT, greater tumour down-staging and volume reduction was observed at Week 14. Timing of surgery, in relation to NACRT, merits further investigation. Trial Registration Number :NCT01325909